Shadow of the Schwarzschild black hole - Villegas, Fulgencio (2022)
In this work, the shadow of the Schwarzschild black hole is studied analytically. The shadow of an object is understood as the shape that said object has in space, seen by an observer when only the properties of space-time are considered. To nd the analytical solution we use the Hamilton-Jacobi equation, the separation of variables method and the introduction of a conserved Carter-type quantity. For the determination of the orbits of constant radius, the impact parameters and the celestial coordinates will be used.